CHANNEL ESTIMATION DESIGN OF MIMOOFDM SYSTEMS USING MMSE FOR IEEE 802.11N WLAN STANDARD - Rima Raissawinda; I Gede Puja Astawa; Yoedy Moegiharto; Ahmad Zainudin; Imam Dui Agusalim (European Scientific Journal, ESJ, 2014)
IEEE 802.11n is the latest development of IEEE 802.11 WLAN communication standard that provides higher significant throughput than IEEE 802.11a/g. With various of transmission channels in wireless communication, has decreased performance of the receiver antennas caused by noise interference and fading channel. Hence, there is a need to analyze channel estimation method to estimate and discover the real condition of channel information between transmitter and receiver for IEEE 802.11n WLAN communication standard. This research simulated the channel estimator using minimum mean squared error (MMSE) algorithm in MIMOOFDM systems with 2x2 and 2x4 schemes. Rectangular shaping filter assumption in time domain is used for the channel approximation due to the multipath Rayleigh fading channel distribution. System performance value is shown in channel impulse response of Tx transmitter to Rx receiver. The simulation results indicate that channel estimator has been working on purpose in MIMO-OFDM system with antenna scheme of 2x2 and 2x4 as well.